The Effect of Mindfulness on Family Stress and Anxiety in Caring for Schizophrenia Patients in City of Sukabumi - Lia Novianty (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: To determine the effect of mindfulness on family stress and anxiety in caring for schizophrenia patients. Methods: This research design is a quasi experiment using a pretest-posttest control group design approach. The study population, families who care for schizophrenia patients with a sample of 30 people using purposive sampling technique. Data analysis using univariate analysis with mean value, and standard deviation, bivariate analysis using paired t-test and independent t-test. Results: Shows that mindfulness practice affects anxiety of control & intervention group (p: 0.000) and stress of control & intervention group (0.000). There is a difference in the mean value of anxiety of the control & intervention group (0.000) and stress of the control & intervention group (0.000). Conclusion: Mindfulness is a psychological intervention that promotes acceptance, understanding, and self-efficacy in families caring for schizophrenia patients, reducing stress, burden, and anxiety it is concluded that there is an effect of mindfulness therapy on family stress and anxiety in caring for schizophrenia patients.